Assessing of organic content in surface sediments of Suez Gulf, Egypt depending on normal alkanes, terpanes and steranes biological markers indicators - Abedel Aziz Elfadly; Omayma E. Ahmed; Mohamed M. El Nady (Egyptian Journal of Petroleum)
The Semi-enclosed Suez Gulf records various signals of high anthropic pressures from surrounding regions and the industrialized Suez countries. The sedimentary hydrocarbons have been studied in 6 coastal stations located in the Gulf of Suez. Non-aromatic hydrocarbons were analyzed by GC/FID and GC/MS to assess organic content in surface sediments of Suez Gulf, Egypt depending on alkanes, terpanes and steranes biological markers indicators. The results showed that the hydrocarbons are originated from multiple terrestrial inputs, biogenic, pyrolytic. Several ratios of hydrocarbons indicated the predominance of petrogenic in combination with biogenic hydrocarbons. Al-Attaqa harbor, Suez oil processing company, Al-Nasr Oil Company, AL-Kabanon and EL-Sukhna of Loloha Beach are the main sources of petroleum contamination.